Psychological mechanisms for enhancing women's social engagement in the context of new Uzbekistan reforms - Huseynova Abira Amanovna (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the psychological mechanisms that enhance women’s social engagement within the framework of the New Uzbekistan reforms. It particularly focuses on factors such as self-efficacy, emotional regulation, recognition, leadership, and social support, which empower women to actively participate in social, economic, and political life. Research Methodology: The research adopts a qualitative-descriptive approach by synthesizing policy reviews, theoretical perspectives, and relevant empirical studies on women’s empowerment and civic participation in Uzbekistan. Data were collected from scholarly publications, governmental reports, and reform policy documents, followed by thematic analysis to identify core psychological and institutional factors. Results: The findings reveal that institutional reforms in Uzbekistan have created favorable conditions for gender equality and civic involvement. Within this context, psychological mechanisms such as self-efficacy, resilience, and leadership capacity help women strengthen motivation, regulate emotions, and sustain active participation. The interaction between supportive institutions and psychological resources significantly contributes to enhancing women’s adaptability and social influence. Conclusions: Women’s empowerment in New Uzbekistan is shaped not only by reforms and institutional frameworks but also by psychological processes that build resilience and leadership. Inclusive pedagogical and policy approaches that acknowledge women’s psychological strengths can accelerate social transformation and gender equality. Limitations: The study is primarily conceptual and relies on secondary data, which may limit generalizability and the ability to capture individual lived experiences. Contribution: This study shows how reforms and psychological resources foster women’s empowerment and civic participation, guiding effective strategies for development.